Alkyl-adamantane as high-density endothermic fuel: Synthesis and thermal cracking performance. (15th September 2022) - Liu, Qing; Pan, Lun; Jia, Tinghao; Zhang, Xiangwen; Zou, Ji-Jun
Graphical abstract: Highlights: A new HED endothermic fuel, HS-1, 3-DMA, was synthesized by alkylation catalyzed by AlCl3 . HS-1, 3-DMA shows high density of 0.89 g·cm −3 and high combustion energy of 42.4 MJ·kg −1 . HS-1, 3-DMA shows high heat sink of 1.93 MJ·kg −1 at 575 °C, 11.6% and 9.7% higher than JP-10 and 1, 3-DMA. The thermal cracking of HS-1, 3-DMA leads to lower coke deposition. Abstract: High-density endothermic fuels have drawn much attention for aerospace vehicles due to their advantage in high density and heat sink. Herein, a new high-density endothermic fuel, hexyl-substituted 1, 3-dimethyl adamantane (HS-1, 3-DMA), was synthesized by alkylation of 1, 3-DMA with hexene catalyzed by AlCl3 . The alkylation reaction conditions (catalyst and its amount, 1, 3-DMA/hexene ratio and reaction temperature) were optimized, and the 1, 3-DMA conversion of 46.0% with HS-1, 3-DMA selectivity of 67.9% can be obtained. Importantly, HS-1, 3-DMA shows high density of 0.89 g·cm −3, high combustion energy of 42.4 MJ·kg −1 and high heat sink of 1.93 MJ·kg −1 at 575 °C (4 MPa), which is 11.6% and 9.7% higher than those of JP-10 and 1, 3-DMA. Moreover, the thermal cracking of HS-1, 3-DMA leads to lower coke deposition, whose amount is ca. 50.0% of JP-10 and 1, 3-DMA. Notably, HS-1, 3-DMA has a higher density and heat sink at low temperatures than that of EHF-80, respectively, while at high temperatures, heat sink of HS-1, 3-DMA is also similar to that of EHF-80. This work provides a promising route to produce high-density endothermic fuel for practical application.